Post mastectomy pain syndrome: A hidden facet among patients underwent mastectomy in Sri Lanka. - Vidura Jayasinghe; Sumal Nandasena (College of Community Physicians of Sri Lanka, 2018)
ABSTRACT Background and objective: The breast cancer is the commonest carcinoma among females in Sri Lanka and majority of them are offered mastectomy as a treatment. However, mastectomy itself cause many complications including Post Mastectomy Pain Syndrome (PMPS). The general objective of present study is to determine the prevalence of PMPS among patients underwent mastectomy and followed up at clinics in National Cancer Institute Maharagama (NCIM), Sri Lanka. Methods: A descriptive cross sectional study was conducted at clinics in NCIM. An interviewer administered questionnaire was used to ascertain socio-demographic characteristics, etc. Perceived pain and severity of pain were assessed with numerical pain scale. The chi-square test was used to find associations of categorical variables. Multivariate analysis was used to identify most important factors associated with the PMPS. Results: The mean age of the study sample was 54.5 years (SD=9.9) and majority of them (65.5 %) were above 50 years. The prevalence of PMPS was 27.5 % among the study population. PMPS was common (p<0.014) among the patients had surgery within 18 months. The prevalence of PMPS was comparatively high among young patients (age≤50 years) than older patients (p<0.001) and patients underwent axillary clearance (p<0.001). Multivariate analysis showed, most important factor that determine the PMPS was age of patients (i.e., patients' age ≤ 50 years). Conclusion: More than one fourth of mastectomy patients were suffering from PMPS. Patients less than 50 years and patients underwent axillary clearance were more likely to suffer from PMPS. Measures need to be taken to identify and manage PMPS. Keywords: Breast cancer, Mastectomy, Post Mastectomy Pain Syndrome.